2006
DOI: 10.1128/aem.72.1.66-70.2006
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Campylobacter Species Cross-Contamination during Handling of Contaminated Fresh Chicken Parts in Kitchens

Abstract: Numerous outbreak investigations and case-control studies for campylobacteriosis have provided evidence that handling Campylobacter-contaminated chicken products is a risk factor for infection and illness. There is currently extremely limited quantitative data on the levels of Campylobacter cross-contamination in the kitchen, hindering risk assessments for the pathogen commodity combination of Campylobacter and chicken meat. An exposure assessment needs to quantify the transfer of the bacteria from chicken to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(108 citation statements)
references
References 22 publications
5
97
1
1
Order By: Relevance
“…In the current study, some TCAM users reported side effects such as hypoglycemia, fatigue, slow heart rhythm, kidney damage, and impotence. Such conditions are of particular concern as diabetes is the leading cause of many chronic diseases including chronic kidney disease; which can progress to kidney failure [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, some TCAM users reported side effects such as hypoglycemia, fatigue, slow heart rhythm, kidney damage, and impotence. Such conditions are of particular concern as diabetes is the leading cause of many chronic diseases including chronic kidney disease; which can progress to kidney failure [12].…”
Section: Discussionmentioning
confidence: 99%
“…Herbal medicines like cinnamon have no clear benefits for diabetics. Nonetheless, it can lead to liver disease, and hemorrhage due to interaction of coumarin substance in cinnamon with blood thinners [12].…”
Section: Introductionmentioning
confidence: 99%
“…only on the eggshell and not in the egg content. But like the situation with broiler meat, it can be expected that the risk for food-borne human campylobacteriosis is much higher via cross-contamination of readyto-eat products than via the consumption of raw or undercooked poultry meat (3,7,8). Like the situation with Salmonella spp., it can be presumed that contamination of the egg content is based mostly on transmission of bacteria from the eggshell to the egg content during the cracking of the eggshell.…”
mentioning
confidence: 99%
“…The EFSA has summarized the available MLST studies from different countries, estimating that 30-50% of the campylobacteriosis cases come from direct consumption and/or handling of chicken meat [3]. The major transmission route might be the consumption of undercooked meat and cross-contamination of meals during the preparation of fresh poultry meat [19]. Moreover, 50-80% of all human Campylobacter infections were attributed to the "chicken reservoir as a whole" [3].…”
Section: Source Attribution Of Human Campylobacter Infectionsmentioning
confidence: 99%